Linking canopy-scale mesophyll conductance and phloem sugar δ13 C using empirical and modelling approaches - Schiestl-Aalto, Pauliina (The New phytologist, 2021)
© 2020 The Authors. New Phytologist © 2020 New Phytologist Trust.